Retenção de inseticida e fungicida em sementes de arroz com o uso de polímeros - Fagundes, Lovane Klein (2016)
The following dissertation has been developed into two chapters: chapter I aimed to evaluate the physiological and sanitary quality of rice seeds treated with fungicide and insecticide coated with polymers, as well as quantify the retention chemicals in seeds that were subjected to a simulated rainfall after planting. Chapter II aimed to verify the effects of the combination of phytosanitary treatment and coating with polymers rice seed germination and force, as well as quantify the potential for waste minimization pesticide and fungicide, released from rice seeds to soaking water by simulating the pre-germinated culture system. Both experiments were conducted in the Laboratório Didático e de Pesquisas em Sementes (LDPS), in the Laboratório de Análises e Resíduos de Pesticidas (LARP), and in the field, all the sites are property of the Universidade Federal de Santa Maria. For such experiments, six rice seeds treatments have been applied, differing between the two chapters only the cultivars, BRS Sinuelo CL® (Chapter I) and EPAGRI 108 (Chapter II), and the phytosanitary treatment. The six treatments were: Control, phytosanitary treatment for Chapter I (fungicide Maxim XL® (active ingredient (i.a.): metalaxyl-M 25 g L-1 + fludioxonil 10 g L-1) and insecticide Cruiser 350® FS (i.a.: thiamethoxam 350 g L-1) and phytosanitary treatment for Chapter II (fungicide Derosal Plus® (i.a.: carbendazim 150 g L-1 + thiram 350 g L-1) and insecticide Cruiser 350® FS (i.a. thiamethoxam 350 g L-1), phytosanitary treatment and coating with polymers: Florite 1127®, Resin Sólid GV5®, Polyseed CF® and Verm Dynaseed®. Assessments were related to physiological and health quality and, through analysis of germination and some seed vigor tests of two rice cultivars sown in substrate paper, sand and soil. In Chapter I, aiming to determine the retention of Active metalaxyl-m and thiamethoxam ingredients, it was mounted a piece of equipment called extractor, consisting of PVC pipes, forming a sand column of 0.10 m where seeding was carried out for five seeds in each tube. It was then simulated a precipitation of 50 mm for 10 min. Samples of the leachate were collected and taken for analysis by liquid chromatography-mass spectrometry. In Chapter II, it was simulated the process of pre-germination, the retention of the active ingredients thiamethoxam and carbendazim was carried out by analyzing the compounds of the soaking water, also by liquid chromatography-mass spectrometry. Completely Randomized Design (CRD) has been applied for the experiments with eight and four replications and the means were compared by Scott Knott s test (p≤0.05). The results in Chapter I and II, regarding chemical seed treatment and polymers coating, did not affect the germination and vigor according to the tests for the two rice cultivars. The polymers Resin Solid GV5®, Polyseed CF®, and Verm Dynaseed® retained 27%, 22%, and 23% more thiamethoxam within rice seeds that were subjected to leaching compared to phytosanitary treatment without the use of polymers. And the retention of thiamethoxam was 12% more, when it was used Florite 1127® and the retention of carbendazim, polymers PolySeed CF® and Vermont Dynaseed contributed 13% and 35% more from seed, as compared to seeds which received no coating with polymers (phitosanitary treatment) via soaking at pre-germinating rice seeds. The combination of chemical seed treatment and coating with polymers can minimize environmental impacts caused by contamination of groundwater by leaching of chemicals or contaminated water originating from different rice cultivation systems.